THE INFLUENCE OF SELF-EFFICACY, INTRINSIC MOTIVATION, ISLAMIC WORK ETHIC, AND PSYCHOLOGICAL WELL-BEING ON PERFORMANCE - Luthfi Arie Widzayanto; Hermin Endratno; Akhmad Darmawan; Totok Haryanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Human resources have an important role in the company achieving its goals. This research aims to examine the influence of self-efficacy, intrinsic motivation, islamic work ethics, and psychological well-being on performance. The research uses primary data and is a type of quantitative research. Permanent nurse at RSI Muhamadiyah Tegal with a population of 155 people, using a purposive sampling method with the criteria being permanent nurses and a minimum work period of 1 year. The response rate in this study was 83.22% or 129 nurses. Questionnaires were distributed via Google Forms to collect data. Using multiple regression analysis via the SPSS 26 application. The results of this study show self-efficacy, Intrinsic motivation, and psychological well-being have a positive and significant effect on performance. However, Islamic work ethic does not affect performance